2019
DOI: 10.3390/cancers11121966
|View full text |Cite
|
Sign up to set email alerts
|

Induction of NK Cell Reactivity against B-Cell Acute Lymphoblastic Leukemia by an Fc-Optimized FLT3 Antibody

Abstract: Antibody-dependent cellular cytotoxicity (ADCC) is a major mechanism by which antitumor antibodies mediate therapeutic efficacy. At present, we evaluate an Fc-optimized (amino acid substitutions S239D/I332E) FLT3 antibody termed 4G8-SDIEM (FLYSYN) in patients with acute myeloid leukemia (NCT02789254). Here we studied the possibility to induce NK cell ADCC against B-cell acute lymphoblastic leukemia (B-ALL) by Fc-optimized FLT3 antibody treatment. Flow cytometric analysis confirmed that FLT3 is widely expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…An anti-FMS-related tyrosine kinase 3 (FLT-3) mAb with Ser239Asp and Ile332Glu mutations is part of a clinical phase I/II trial to treat patients with acute myeloid leukemia (AML) ( identifier: NCT02789254). Recent in vitro studies using this FLT-3 mAb suggested that it could also be suitable for the treatment of B cell acute lymphoblastic leukemia (B-ALL) [ 80 ]. A screen that aimed to elucidate increased CD16A binding/decreased off rate and also prevent increased affinity for inhibitory CD32B found that the combination of Phe243Leu, Arg292Pro, Tyr300Leu, Val305Ile, and Pro396Leu (referred to as Variant 18) achieved this [ 81 ].…”
Section: Therapeutic Mab Engineeringmentioning
confidence: 99%
“…An anti-FMS-related tyrosine kinase 3 (FLT-3) mAb with Ser239Asp and Ile332Glu mutations is part of a clinical phase I/II trial to treat patients with acute myeloid leukemia (AML) ( identifier: NCT02789254). Recent in vitro studies using this FLT-3 mAb suggested that it could also be suitable for the treatment of B cell acute lymphoblastic leukemia (B-ALL) [ 80 ]. A screen that aimed to elucidate increased CD16A binding/decreased off rate and also prevent increased affinity for inhibitory CD32B found that the combination of Phe243Leu, Arg292Pro, Tyr300Leu, Val305Ile, and Pro396Leu (referred to as Variant 18) achieved this [ 81 ].…”
Section: Therapeutic Mab Engineeringmentioning
confidence: 99%
“…In recent years, a personalized treatment approach involving the following has contributed to the progress of adult ALL therapy: response to minimal residual disease and disease genetics; adopting pediatric-inspired regimens in younger adults; advances in transplantation; incorporation of new treatments and tyrosine kinase inhibitors found in frontline regimens; as well as adoptive cellular therapy (Aldoss and Stein, 2018;Pillai et al, 2019). In particular, antibody-based therapies, such as monoclonal antibodies and antibody-drug conjugates have shown promising activity profiles for the treatment of ALL (Phelan and Advani, 2018;Schmied et al, 2019). Introduction of these strategies in the frontline setting has been ongoing and will likely unravel significant benefits for ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Natural killer (NK) cell-based immunotherapy represents one of the novel immunotherapeutic strategies recently, unleashing immune suppression of NK cells to attack various cancers [10][11][12]. With the progressive elucidation of NK cell immunobiology and the development of manipulative techniques, the field of NK cellbased immunotherapy in hematological malignancies has been expanding and accelerating over the past years, including adoptive NK cell transfer [13][14][15][16], chimeric antigen receptor (CAR)-modified NK cells [17][18][19][20][21][22], antibodies [23][24][25], cytokines [26,27] and drug treatment [28][29][30][31]. Despite remarkable progress has been made, the application in AML is still at the initial stage.…”
Section: Introductionmentioning
confidence: 99%